Antifactor Xa levels vs. activated partial thromboplastin time for monitoring unfractionated heparin. A pilot study. (6th July 2016) - Samuel, S.; Allison, T. A.; Sharaf, S.; Yau, G.; Ranjbar, G.; Mckaig, N.; Nguyen, A.; Escobar, M.; Choi, H. A
Summary: What is known and objectives: The two most common methods for monitoring unfractionated heparin (UFH) infusion are the activated partial thromboplastin time (aPTT) and the antifactor Xa heparin assay (anti‐Xa). The purpose of this study is to compare the performance of an aPTT protocol vs. an anti‐Xa protocol in adult patients as defined by the time to reach therapeutic range, the percentage of time the values were within the goal range and the number of times laboratory monitoring was conducted. We then analysed the discordance between paired values of anti‐Xa and aPTT. Methods: This was a single‐centre prospective cohort pilot study conducted from 1 September 2013 to 31 May 2014. Results: Eighty‐five patients were treated with UFH infusion, aPTT monitoring ( n = 48), anti‐Xa monitoring ( n = 37). The number of times aPTT and anti‐Xa values were ordered was (median, IQR) 14 (2–34) vs 7 (2–76); P = 0·23. The time to reach therapeutic range in hours was (mean, SD) 22 (20) aPTT vs 15 (13) anti‐Xa; P = 0·08. Therapeutic range (>50–100% of the time) was achieved in only 5 (10%) patients in the aPTT group vs. 21 (57%) in the anti‐Xa group; P < 0·01. Supratherapeutic values (>50–100%) were observed in 38 (78%) patients in the aPTT group vs. 14 (38%) in the anti‐Xa group; P < 0·01. The discordance between aPTT and anti‐Xa was evaluated using 234 paired values from 37 patients. There was discordance between anti‐Xa and aPTT values 57% of the time. Two patients had bleeding complications requiring blood transfusion or discontinuation of post‐pilot protocol. What is new and conclusion: Utilizing an anti‐Xa protocol to monitor heparin infusion showed favourable results compared with utilizing an aPTT protocol by maintaining values within the therapeutic goal range. The most common discordant pattern in our study was a disproportionate prolongation of aPTT to anti‐Xa values. Patients with discordant values presenting with high aPTT to normal anti‐Xa values may have an increased risk of bleeding complications. Abstract : What is known and objectives The two most common methods for monitoring unfractionated heparin (UFH) infusion are the activated partial thromboplastin time (aPTT) and the antifactor Xa heparin assay (anti‐Xa). The purpose of this study is to compare the performance of an aPTT protocol vs. an anti‐Xa protocol in adult patients as defined by the time to reach therapeutic range, the percentage of time the values were within the goal range and the number of times laboratory monitoring was conducted. We then analysed the discordance between paired values of anti‐Xa and aPTT.Methods This was a single‐centre prospective cohort pilot study conducted from 1 September 2013 to 31 May 2014.Results Eighty‐five patients were treated with UFH infusion, aPTT monitoring ( n = 48), anti‐Xa monitoring ( n = 37). The number of times aPTT and anti‐Xa values were ordered was (median, IQR) 14 (2–34) vs 7 (2–76); P = 0·23. The time to reach therapeutic range in hours was (mean, SD) 22 (20) aPTT vs 15 (13) anti‐Xa; P = 0·08. Therapeutic range (>50–100% of the time) was achieved in only 5 (10%) patients in the aPTT group vs. 21 (57%) in the anti‐Xa group; P < 0·01. Supratherapeutic values (>50–100%) were observed in 38 (78%) patients in the aPTT group vs. 14 (38%) in the anti‐Xa group; P < 0·01. The discordance between aPTT and anti‐Xa was evaluated using 234 paired values from 37 patients. There was discordance between anti‐Xa and aPTT values 57% of the time. Two patients had bleeding complications requiring blood transfusion or discontinuation of post‐pilot protocol.What is new and conclusion Utilizing an anti‐Xa protocol to monitor heparin infusion showed favourable results compared with utilizing an aPTT protocol by maintaining values within the therapeutic goal range. The most common discordant pattern in our study was a disproportionate prolongation of aPTT to anti‐Xa values. Patients with discordant values presenting with high aPTT to normal anti‐Xa values may have an increased risk of bleeding complications.